Extracellular glypican‐1 affects tumor progression and prognosis in esophageal cancer - Rie Shibata; Hirotaka Konishi; Tomohiro Arita; Yusuke Yamamoto; Hayato Matsuda; Taiga Yamamoto; Takuma Ohashi; Hiroki Shimizu; Shuhei Komatsu; Atsushi Shiozaki; Takeshi Kubota; Hitoshi Fujiwara; et al. (Cancer Medicine)
Abstract Introduction Cells are covered with a glycan surface layer that is referred to as the glycocalyx (GCX). It has been reported that the formation of the GCX is promoted on cancer cells and is associated with tumor growth and metastasis. Heparan sulfate proteoglycan glypican‐1 (GPC1) is a core protein of the GCX that is overexpressed in esophageal squamous cell carcinoma (ESCC) and is involved in the development and progression of cancer cells. The purpose of the present study is to analyze the utility of GPC1 as a new biomarker ralated to glycocalyx that reflects therapeutic effect and prognosis of ESCC. Methods We measured the concentration of GPC1 protein in preoperative plasma from advanced esophageal cancer patients and examined its relationships with clinicopathological factors and therapeutic efficacy, and the effects of extracellular GPC1 were investigated. Results The following clinical factors were significantly correlated with the preoperative high GPC1 concentration: male, tumor size ≥30 mm, venous invasion, pT factor ≥2, pStage ≥3, residual tumor, and distant metastatic recurrence. Both overall and recurrence‐free survival were significantly worse in the high GPC1 group. Extracellular GPC1 protein concentration reflected intracellular GPC1 expression. Furthermore, we examined the effects of extracellular recombinant human (rh)GPC1 on ESCC cells, and found that extracellular rhGPC1 affects cell motility, including migration and invasion. Conclusions These results demonstrated the utility of extracellular GPC1 as a biomarker, which can be assayed from a less invasive blood sample‐based liquid biopsy. Extracellular GPC1 protein plays a role in both tumor cell motility and cancer progression. Thus, plasma GPC1 is a useful biomarker for esophageal cancer progression and may be a potential candidate of therapeutic target.